Rancang Bangun Aplikasi PPDB Berbasis Laravel pada SMK Darun Nadwah As-Salam - Oky Chandra Wiranata; Sigit Auliana; Basuki Rakhim Setya Permana (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2025)
The development of information technology has had a significant impact on various sectors, including education. One of its implementations is the application of a web-based New Student Admission (PPDB) system to improve the efficiency and accuracy of the registration process. SMK Darun Nadwah As-Salam has previously used a manual system with paper forms, which often causes delays and data recording errors. This condition encourages the need to develop a more effective and integrated web-based PPDB system. This study applies the Software Development Life Cycle (SDLC) Waterfall model, which consists of requirement analysis, system design, implementation, testing, and maintenance stages. The application was developed using the Laravel framework, PHP programming language, and MySQL database, with Visual Studio Code as the editor and Laragon as the local server. Data were collected through observation, interviews, and documentation. The results show that the web-based PPDB application can simplify the registration process, reduce input errors, and speed up data processing for prospective students. Moreover, the system can be accessed online, allowing applicants to register without visiting the school in person. In conclusion, the implementation of a web-based PPDB application at SMK Darun Nadwah As-Salam can improve the efficiency, accuracy, and transparency of the new student admission process, while supporting digital transformation in education.